Alignment and the syllable coda condition in Malay: an optimality account - Zaharani Ahmad (Penerbit UKM, 2004)
It has long been observed that the basic structure of the Malay syllable is (C)V(C) (Abdullah 1974, Yunus 1980, Farid 1980), allowing only a single segment to occupy constituents of the syllable. Although Malay may have single-member codas, there is a restriction in the language which prohibits a small class of consonants from occupying the coda position. In the phonological analysis of syllable structures, the prohibition of some segments in the coda is governed by the Syllable Coda Condition (Itofl 1986). The aim of this paper is to account for the effects of the Syllable Coda Condition in Malay, and the present analysis is couched in the constraint-based approach of Optimality Theory (henceforth OT) (Prince and Smolensky 2004, McCarthy and Prince 1993a,b). The paper is organised as follows. Section 2.0 outlines briefly the statement of the problem and section 3.0 demonstrates the process of syllabification within the OT framework. The effects of the Syllable Coda Condition which are analysed in terms of alignment constraint (Itofl and Mester 1994) is explored in section 4.0.